Arsenic and lead in the indoor residential settings of different socio-economic status; assessment of human health risk via dust exposure - Ali, Nadeem; Eqani, Syed Ali Musstjab Akber Shah; Nazar, Ehtisham; Alhakamy, Nabil A.; Rashid, Muhammad Imtiaz; Shahzad, Khurram; Zeb, Jahan; Shen, Heqing; Ismail, Iqbal Mohammad Ibrahim; Albar, Hussain Mohammed Salem Ali (Environmental science and pollution research international, 2021)
In the present study, occurrence of arsenic (As) and lead (Pb) is reported in rural and urban household dust (floor and AC filter dust) of the Kingdom of Saudi Arabia (KSA). Several studies have found concerning concentrations of these toxic metals in indoor dust from different countries, but data from this region is missing. The association between studied toxic metals and different socioeconomic parameters was investigated. Furthermore, health risk associated with these toxic metals via dust exposure was evaluated for the Saudi population. Mean concentration of Pb was several times higher than As in both types of dust samples. AC filter dust was more contaminated with these metals than floor dust. Levels of Pb were up to 775 ppm in AC filter dust from urban areas, while 167 ppm in rural AC filter dust. Different socioeconomic parameters did not influence much on the presence of studied metals in both AC and floor dust. To estimate health risk from contaminated dust hazardous index (HI), hazardous quotient (HQ), and incremental lifetime cancer risk (ILCR) via dust ingestion, inhalation, and dermal contact was calculate using USEPA equations. The ILCR range for both toxic metals was within the tolerable range of reference values of USEPA (1 × 10 −5 to 5 × 10 −7 ). Nonetheless, HI was close to 1 for Pb via dust exposure for young urban children, which signifies the risk of non-carcinogenic health problems in studied area. Graphical abstract